2018
DOI: 10.1016/j.phrs.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib prevents lung cancer metastasis by inhibiting M2-like polarization of macrophages

Abstract: Although M2-like tumor-associated macrophages (TAMs) have been considered as a vital therapeutic target in cancer therapy due to their role in promoting tumor progression and metastasis, very few compounds have been identified to inhibit M2-like polarization of TAMs. Here, we showed that Imatinib significantly prevented macrophage M2-like polarization induced by IL-13 or IL-4 in vitro, as illustrated by reduced expression of cell surface marker CD206 and M2-like genes, including Arg1, Mgl2, Mrc1, CDH1, and CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Past research has reported that imatinib, a tyrosine kinase inhibitor, inhibited M2 macrophage polarization by blocking the phosphorylation of STAT6 and nuclear translocation, thus preventing lung cancer metastasis. 51 In the present study, myostatin reduced M2 macrophage polarization by inhibiting the JAK1/STAT6 pathway in macrophage cells differentiated from U937 monocytes. Macrophages that respond to environmental changes, including the presence of various cytokines and growth factors, have been implicated in M1/M2 polarization.…”
Section: Discussionsupporting
confidence: 45%
“…Past research has reported that imatinib, a tyrosine kinase inhibitor, inhibited M2 macrophage polarization by blocking the phosphorylation of STAT6 and nuclear translocation, thus preventing lung cancer metastasis. 51 In the present study, myostatin reduced M2 macrophage polarization by inhibiting the JAK1/STAT6 pathway in macrophage cells differentiated from U937 monocytes. Macrophages that respond to environmental changes, including the presence of various cytokines and growth factors, have been implicated in M1/M2 polarization.…”
Section: Discussionsupporting
confidence: 45%
“…Zhang et al . found that imatinib also can inhibit macrophage M2‐like polarization both in vitro and in vivo, which contributes to its anti‐metastatic function in lung cancer . In addition, Shinya et al .…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al found that imatinib also can inhibit macrophage M2-like polarization both in vitro and in vivo, which contributes to its anti-metastatic function in lung cancer. 45 In addition, Shinya et al found that targeting platelet-derived growth factor signaling between cancer cells undergoing EMT and CAFs was a promising therapeutic target to inhibit cancer progression and improve patient prognosis. 46 Our results showed that CAFs and TAMs were significantly related to STAS and may be effective therapeutic targets in patients with STAS.…”
Section: Discussionmentioning
confidence: 99%
“…What we do know, however, is that compounds like apigenin that attenuate the CCL2/CCR2 axis would slow the aggressive nature of TNBC and hormone positive breast cancers (27,28) by attenuating invasion, metastasis, EMT and the development of drug resistance (59)(60)(61)(62). CCL2 inhibitors have been tested in various tumors, tumor cells and xenograft models with CCL2 lowering effects brought about by losartan (63) anlotinib (64) imatinib (65) zoledronic acid (66) oroxylin A (67) aspirin (68) natural compounds in coffee (kahweol acetate, cafestol) (69) or conophylline from Ervatamia microphylla (70) which can reduce invasive inflammatory tumor infiltration. The mechanism of action for CCL2 reducing agents may center around the modification of upstream or downstream targets such as PLEK2/EGRF (71) HER2-EGF/HRG, PI3K-NF-kB axis (27) SRC, PKC (58) the neddylation pathway (72) or the well-known mitogen-activated protein kinases and phosphatidylinositol 3-kinase/Akt cell signaling pathways (73).…”
Section: Discussionmentioning
confidence: 99%